Felipe Boero : (Buenos Aires, 1-05-1884; ibid, 9- 08-1958) - Mondolo, Ana María (2006)
Fil: Mondolo, Ana María. Pontificia Universidad Católica Argentina. Facultad de Artes y Ciencias Musicales; Argentina